ADVERTISING PHOTOGRAPHY - Vakhtang Egiazarov; F. X. Egiazarov (The Conference Hub, 2025)
Advertising photography is a field of photographic art that highlights the best features of a product or service. A well-executed advertising photo is the best advertisement for any marketing company.